2012
DOI: 10.1039/c1fd00054c
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics in protic ionic liquids: A combined optical Kerr-effect and dielectric relaxation spectroscopy study

Abstract: The structure and dynamics of ionic liquids (ILs) are unusual due to the strong associations of the ions and counter ions. These microscopic properties determine the bulk transport properties critical to applications of ILs such as advanced fuel cells. Here the terahertz dynamics and slower 10 relaxations of simple alkylammonium nitrate protic ionic liquids (PILs) are studied using femtosecond optical Kerr-effect spectroscopy, dielectric relaxation spectroscopy, and terahertz time-domain spectroscopy. The obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 48 publications
5
71
0
Order By: Relevance
“…However, in the light of new results it seems more appropriate to use a so-called "constant-loss" term for this region (Figure 4) consistent with studies of other strongly interacting liquids [28]. This mainly translational mode is associated with the rattling of molecules in their cage of surrounding neighbors superimposed on the formation and decay of these cages.…”
Section: Short-time Dynamicsmentioning
confidence: 72%
See 1 more Smart Citation
“…However, in the light of new results it seems more appropriate to use a so-called "constant-loss" term for this region (Figure 4) consistent with studies of other strongly interacting liquids [28]. This mainly translational mode is associated with the rattling of molecules in their cage of surrounding neighbors superimposed on the formation and decay of these cages.…”
Section: Short-time Dynamicsmentioning
confidence: 72%
“…To capture the wide time-span of intermolecular dynamics, two OKE set-ups were employed. The faster dynamics were measured using a 7 nJ, 20 fs pulse (Coherent Mira-SEED) [27] with weaker relaxations at longer times recorded using a regeneratively-amplified setup (Coherent Mantis Legend USX) with a 1 µJ pulse stretched to a duration of ∼ 1 ps [28].…”
Section: Optical Kerr-effect Spectroscopymentioning
confidence: 99%
“…Additionally, a small high-frequency D equation peaking outside the present frequency range is required to summarize the small contributions from intermolecular vibrations and librations at THz frequencies that extend below 89 GHz. 26 Data analysis revealed that for all mixture spectra a sum of two modes (n = 2 in eqn (3)) yielded the best fit ( Fig. 1 and 2).…”
Section: Choice Of Fit Modelmentioning
confidence: 88%
“…13 The similar friction coefficients also suggest that at least down to x EAN E 0.7 the [EtNH 3 ] + cation relaxes via large-angle jumps as the pure IL. 26,38 3.3.2 Amplitude. Using eqn (5) the conclusions made in Section 3.2.1 can be confirmed and extended quantitatively.…”
Section: Amplitudesmentioning
confidence: 99%
“…The static structure of ionic liquids has been investigated by X-ray/neutron scattering and molecular simulation techniques to obtain the static structure factor S(Q) and the radial distribution function g(r). [1][2][3][4] Studies of dynamics have also been carried out by nuclear magnetic resonance (NMR), [5][6][7] optical Kerr effect, low-frequency Raman THz and far-IR spectroscopies, [8][9][10][11][12] dielectric relaxation, [11][12][13] and molecular dynamics simulations. 14 Hayamizu et al reported the diffusion coefficients of cation and anion in various ionic liquids by pulsed-gradient spin-echo (PGSE) NMR, and the results were related to macroscopic properties such as viscosity and ionic conductivity.…”
mentioning
confidence: 99%